Supercapacitors: A Flexible Ionic Liquid Gelled PVA‐Li2SO4 Polymer Electrolyte for Semi‐Solid‐State Supercapacitors (Adv. Mater. Interfaces 15/2015). Issue 15 (19th October 2015) - Zhang, Xing; Wang, Liangliang; Peng, Jing; Cao, Pengfei; Cai, Xiaosheng; Li, Jiuqiang; Zhai, Maolin
<x xml:space="preserve">Abstract</x> M. Zhai and co‐workers report on their preparation of a novel ionic liquid gelled PVA‐Li2SO4 flexible gel polymer electrolyte (FGPE) in article number 1500267. The FGPE can be used as both an electrolyte and as a separator for supercapacitors when sandwiched between two carbon electrodes. The fabricated supercapacitor can withstand multi‐mechanical bending cycles without suffering any decrease in its electrochemical properties. Potential applications of the system include its use in power sources of wearable electronics.